O exame de convenção coletiva ou acordo coletivo pela Justiça do Trabalho após a Lei nº13.467/17. - Santos, Cássia Barata de Moraes (2019)
This research originated from Law nº 13.467/17, which added § 3º to art. 8º of the Consolidation of Labor Laws (CLT). This new normative command imposed limits on the performance of the Labor Court at the time of the examination of collective agreement, ie, limited the analysis of these negotiated legal instruments to the requirements of validity of the legal business, specified in art. 104 of the Civil Code. In addition, this new law created a new principle with the purpose of consolidating the delimitation of the action of the Labor Justice, called the principle of minimum intervention in the autonomy of collective will and established an unlimited list of negotiable rights in art. 611-A of the CLT. In order to deepen the validity requirements of the legal business, highlighting the collective autonomy of the will and the applicability of these elements to the Collective Labor Law, the research analyzes the amplitude of the elements that must be taken into consideration by the Labor Court at examination of the negotiated standard, presenting to the Labor Law operator a comparative analysis of the peculiarities of Civil Law referring to the limits of private autonomy of will to the guidelines of the Constitution of the Republic, highlighting the principles of human dignity and the social function of property. In addition, procedural issues were analyzed in order to ensure broad access to justice and the independence of the judiciary. Given the new legal scenario, established from Law no. 13.467 / 17, after analyzing the vast bibliography and elected jurisprudence of the Federal Supreme Court, the Labor Law operators, especially the Labor Justice organs, will have in hand elements that will guide the examination of collective agreement or collective agreement from the Law nº. 13.467/17, especially with regard to the limits of the negotiated over the legislated in view of the current legal system in Brazil.